Catching Christmas - Blackstock, Terri 1957- (Thorndike, Maine : Center Point Large Print, 2018)
"New York Times bestselling author Terri Blackstock tells the rich and heartwarming story of a cab driver, a young attorney, and the elderly woman who will stop at nothing to give her granddaughter one special gift for Christmas"- -
Keywords: Taxicab drivers -- Fiction; Women lawyers -- Fiction; Grandmothers -- Fiction; Man-woman relationships -- Fiction; Christmas fiction; Christian fiction